Transparent conductive film

The transparent conductive film addresses durability and sticking issues in resistive touch panels by optimizing surface characteristics and layer configurations, resulting in improved performance and appearance.

JP2024176378AInactive Publication Date: 2024-12-19TOYOBO CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023094870
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-08
Publication Date
2024-12-19
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing transparent conductive films for resistive touch panels face challenges in durability against continuous input, sticking resistance, and appearance issues such as white spots and unevenness, which affect their performance and reliability.

Method used

A transparent conductive film with specific surface characteristics, including average arithmetic mean height (AVSa) and maximum peak height (AVSp) within defined ranges, combined with a curable resin layer and functional layer, enhances durability and reduces sticking, while maintaining a smooth and uniform appearance.

Benefits of technology

The film provides excellent continuous input durability, improved sticking resistance, and a clear, uniform surface, ensuring reliable operation of resistive touch panels without visible white spots.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024176378000001_ABST
    Figure 2024176378000001_ABST
Patent Text Reader

Abstract

To provide a transparent conductive film excellent in all of continuous input durability, anti-sticking property, and appearance.SOLUTION: The transparent conductive film of the present invention is a transparent conductive film laminated with a transparent conductive film of an indium tin compound oxide on at least one face of a transparent plastic film substrate, where the average arithmetical average height (AVSa) of the transparent conductive film is 2nm or more and 50 nm or less, the average maximum peak height (AVSp) of the transparent conductive film is 150 nm or more and 1,000 nm or less, the average protrusion width found by a test method 1 on a surface of the transparent conductive film side and a surface opposite to a surface laminated with the transparent conductive film is 12 μm or less, the laminate strength of the transparent conductive film found by a test method 2 is 450 N / 15 mm or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transparent conductive film in which a transparent conductive film of indium-tin composite oxide is laminated on a transparent plastic film substrate. [Background technology]

[0002] Transparent conductive films, which are made by laminating a transparent, low-resistance thin film onto a transparent plastic film substrate, are widely used in electrical and electronic applications that utilize their electrical conductivity, such as in flat panel displays such as liquid crystal displays and electroluminescence (EL) displays, and as transparent electrodes in touch panels.

[0003] A resistive touch panel is a combination of a fixed electrode made of a glass or plastic substrate coated with a transparent conductive thin film, and a movable electrode (called a film electrode) made of a plastic film coated with a transparent conductive thin film, and is used by overlapping them on the top of a display. When the film electrode is pressed with a finger or pen (called input), the transparent conductive thin films of the fixed electrode and the film electrode come into contact with each other, and the input position is recognized.

[0004] Patent Document 1 discloses a transparent conductive film in which a transparent conductive thin film made of an indium-tin composite oxide or a tin-antimony composite oxide is laminated on a plastic film, and the transparent conductive thin film surface has a center line average roughness (Ra) of 0.1 to 0.5 μm. Patent Document 2 discloses a transparent conductive film including a support and a transparent conductive layer formed on one surface of the support, in which the surface on the transparent conductive layer side has a surface roughness Ra1 of 7 to 20 nm and the number of protrusions with a height of 250 nm or more is 140 / mm. 2 A transparent conductive film that satisfies the above requirements has been disclosed. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 4961697 [Patent Document 2] Patent No. 6425598 Summary of the Invention [Problem to be solved by the invention]

[0006] Recently, there has been an increase in the demand for resistive touch panels. For example, resistive touch panels are required to have the property of being able to continue inputting even when touched lightly after inputting with a relatively strong force using a pen or finger (continuous input durability). It is also important for resistive touch panels to prevent the fixed electrode and film electrode from sticking together (anti-sticking). Furthermore, because the transparent conductive film is located on the outermost layer of the resistive touch panel, it is required for the transparent conductive film to have a good appearance (clear without any whitish tint, uniform across the entire surface without any unevenness).

[0007] The inventors of the present invention verified that the transparent conductive film described in Patent Document 1 has good anti-sticking properties but poor durability to continuous input, and the entire surface appears whitish due to white spots caused by protrusions on the transparent conductive film. The transparent conductive film described in Patent Document 2 has good durability to continuous input and good appearance, but does not have satisfactory anti-sticking properties.

[0008] It is therefore an object of the present invention to provide a transparent conductive film which is excellent in all respects: durability against continuous input, anti-sticking properties and appearance. [Means for solving the problem]

[0009] The present invention has been made in view of the above circumstances, and the transparent conductive film of the present invention, which is able to solve the above problems, has the following configuration. [1] A transparent conductive film comprising a transparent plastic film substrate and a transparent conductive film of indium-tin composite oxide laminated on at least one surface of the substrate, The transparent conductive film has an average arithmetic mean height (AVSa) of 2 nm or more and 50 nm or less, The transparent conductive film has an average maximum peak height (AVSp) of 150 nm or more and 1000 nm or less, the average protrusion width on the transparent conductive film side surface and on the surface opposite to the surface on which the transparent conductive film is laminated, determined by the following Test Method 1, is 12 μm or less; A transparent conductive film, wherein the laminate strength of the transparent conductive film determined by the following Test Method 2 is 450 N / 15 mm or more. [Test method 1] Particle analysis is performed using a three-dimensional surface profile measuring device, VertScan (measurement conditions: wave mode, measurement wavelength 560 nm, objective lens 50x, field of view 188.709 μm × 141.496 μm) in the following steps (i) to (v). (i) The cross-sectional area of ​​all protrusions at a height of 0.1 μm from the lowest point on the measurement surface (T c This measurement is performed on both the transparent conductive film side surface and the surface opposite to the surface on which the transparent conductive film is laminated, and the sum of the cross-sectional areas of all protrusions on the transparent conductive film side surface and the surface opposite to the surface on which the transparent conductive film is laminated is taken as the cross-sectional area of ​​all protrusions (T c ) (ii) The average cross-sectional area of ​​all protrusions (the total number of protrusions is N p Then, T c / N p ) is required. (iii) Mean value (T c / N p ) and the average value (T c / N p ) does not include protrusions with a cross-sectional area of ​​1 / 10 or less of the (iv) From the protrusions remaining in (iii), the top 20% and bottom 20% of the protrusions are further removed in order of largest cross-sectional area. (v) For the protrusions remaining in (iv), the average cross-sectional area (A) is calculated, and this value is substituted into the following formula (1) to calculate the average protrusion width (B). Formula (1): Average protrusion width (B) = 2 × (A÷π) 0.5 [Test method 2] A urethane-based two-component curing adhesive (containing 4% by mass of ethyl acetate as a solvent) is applied to the transparent conductive film side surface of the transparent conductive film using wire bar #5, and then heated at 60°C for 1 minute. The adhesive-coated surface of the transparent conductive film and the PET surface of a PET film (thickness 100 μm) are then bonded together at 60°C by dry lamination (0.3 MPa, width 70 cm), and aged at 40°C for 4 days to obtain a laminate for evaluation. The obtained laminate is cut into a width of 15 mm and a length of 150 mm to prepare a test piece, and a T-peel test is performed under conditions of a temperature of 23°C, a relative humidity of 65%, and a peel speed of 100 mm / min to measure the maximum load. [2] The transparent conductive film has a thickness of 10 nm or more and 100 nm or less; The transparent conductive film has a tin oxide concentration of 0.5% by mass or more and 11% by mass or less, The transparent conductive film has a static friction coefficient of 1.00 or less; The transparent conductive film according to [1], wherein the transparent conductive film has a dynamic friction coefficient of 0.80 or less. [3] The transparent conductive film according to [1] or [2], wherein the crystallinity of the transparent conductive film is 70% or more. [4] A curable resin layer is provided between the transparent plastic film substrate and the transparent conductive film, The transparent conductive film according to any one of [1] to [3], further comprising a functional layer on the opposite side of the transparent plastic film substrate to the side on which the transparent conductive film is present. [5] The transparent conductive film according to [4], wherein the curable resin layer contains at least one type of particles selected from inorganic particles and organic particles. [6] The transparent conductive film according to [4] or [5], wherein the static friction coefficient of the functional layer is 0.70 or less and the dynamic friction coefficient of the functional layer is 0.50 or less. [7] The transparent conductive film according to any one of [4] to [6], wherein the functional layer contains at least one type of particles selected from inorganic particles and organic particles. [8] The transparent conductive film according to any one of [1] to [7], which has an easy-adhesion layer on at least one side of the transparent plastic film substrate. [9] The transparent conductive film according to [4], wherein an easy-adhesion layer is disposed either between the transparent plastic film substrate and the curable resin layer or between the transparent plastic film substrate and the functional layer, or both. Effect of the Invention

[0010] According to the present invention, there is provided a transparent conductive film which is excellent in all of durability against continuous input, anti-sticking properties and appearance. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic side view showing an example of the transparent conductive film of the present invention. [Diagram 2] FIG. 2 is a schematic side view showing another example of the transparent conductive film of the present invention. [Diagram 3] FIG. 3 is a schematic side view showing another example of the transparent conductive film of the present invention. [Figure 4] FIG. 4 is a schematic side view showing another example of the transparent conductive film of the present invention. [Diagram 5] FIG. 5 is a schematic diagram of an apparatus showing an example of the film forming method of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] <1. Transparent conductive film> The transparent conductive film according to the present invention will be specifically described below with reference to FIGS. 1 to 4 showing examples. However, the present invention is not limited to the illustrated examples, and can be modified appropriately within the scope of the above and below, and all of these are included in the technical scope of the present invention. As shown in FIG. 1, the transparent conductive film 20 of the present invention has a structure in which a transparent conductive film 5 is laminated on at least one surface of a transparent plastic film substrate 7. Since the transparent conductive film 20 has the transparent conductive film 5 on its surface, the transparent conductive film according to the present invention can be widely used in applications that utilize its conductivity, such as flat panel displays such as liquid crystal displays and electroluminescence (EL) displays, and transparent electrodes for touch panels, in electrical and electronic applications.

[0013] As shown in the transparent conductive film 20 of FIG. 1, the transparent conductive film 20 of the present invention preferably has a curable resin layer 6 between the transparent plastic film substrate 7 and the transparent conductive film 5. By laminating the transparent conductive film 5 on the transparent plastic film substrate 7 via the curable resin layer 6, the curable resin layer 6 plays the role of a base layer for the transparent conductive film 5, and the curable resin layer 6 can block the precipitation of monomers and oligomers generated from the transparent plastic film substrate 7 on the transparent conductive film 5. This improves the appearance of the transparent conductive film 20. Furthermore, by providing the curable resin layer 6, it is possible to improve the durability against continuous input and the sticking resistance.

[0014] As shown in the transparent conductive film 20 in Fig. 1, the transparent conductive film 20 of the present invention preferably has a functional layer 8 on the side of the transparent plastic film substrate 7 opposite to the side on which the transparent conductive film 5 is present. The functional layer 8 can easily impart properties such as a good appearance, smooth input properties that do not catch fingers, and resistance to scratches when inputting with a pen or the like to the transparent conductive film 20. The ability to prevent scratches when inputting is desirably 2H or more when the pencil hardness is measured in accordance with JIS K5600-5-4:1999.

[0015] Although the curable resin layer 6 and / or the functional layer 8 are not necessarily required, providing these layers can improve the durability against continuous input, the sticking resistance, the appearance, etc. Also, by appropriately changing the configuration of the curable resin layer 6 and the functional layer 8 (for example, the number average particle size and content of the particles optionally contained, the content of the leveling agent, the thickness of each layer, etc.), it is possible to adjust the AVSa, AVSp, average protrusion width, and laminate strength of the transparent conductive film.

[0016] The transparent conductive film 20 of the present invention preferably has an easy-adhesion layer (e.g., 9A, 9B) on at least one side of the transparent plastic film substrate 7. The easy-adhesion layers (9A, 9B) play a role in firmly adhering the transparent plastic film substrate 7 to the cured resin layer 6, or the transparent plastic film substrate 7 to the functional layer 8. The strong adhesion can improve the durability against continuous input and prevent damage to the functional layer. Furthermore, by providing a layer such as the easy-adhesion layer 9A between the transparent plastic film substrate 7 and the cured resin layer 6, the force applied in the thickness direction to the transparent conductive film 5 can be dispersed, so that cracks, peeling, wear, etc., on the transparent conductive film in the continuous input durability test can be prevented.

[0017] In a more preferred embodiment, the easy-adhesion layer is disposed between the transparent plastic film substrate 7 and the curable resin layer 6 or between the transparent plastic film substrate 7 and the functional layer 8, or both. The transparent conductive film 20 in FIG. 2 has a structure in which the transparent plastic film substrate 7 and the curable resin layer 6 are laminated (adhered) through an easy-adhesion layer 9A. The transparent conductive film 20 in FIG. 3 has a structure in which the transparent plastic film substrate 7 and the functional layer 8 are laminated (adhered) through an easy-adhesion layer 9B. The transparent conductive film 20 in FIG. 4 has a structure in which the transparent plastic film substrate 7 and the curable resin layer 6 are laminated (adhered) through an easy-adhesion layer 9A, and the transparent plastic film substrate 7 and the functional layer 8 are laminated (adhered) through an easy-adhesion layer 9B. The easy-adhesion layer may or may not be in direct contact with each of the transparent plastic film substrate 7, the curable resin layer 6, and the functional layer 8.

[0018] The total light transmittance of the transparent conductive film is preferably 70% or more and 95% or less, more preferably 80% or more and 93% or less, and even more preferably 85% or more and 90% or less.

[0019] The continuous input durability of the transparent conductive film is preferably 7,500 times or more, more preferably 15,000 times or more, and further preferably 30,000 times or more. The higher the value of the continuous input durability, the more preferable it is, and there is no particular upper limit.

[0020] The transparent conductive film of the present invention has excellent anti-sticking properties, and therefore can prevent the fixed electrode and the film electrode from sticking together (sticking) when the film electrode is pressed and slid with a finger, pen, etc. in a resistive touch panel. This allows accurate control of the touch panel input position.

[0021] The transparent conductive film of the present invention is uniform over the entire surface without unevenness. Furthermore, the average value of the transmitted image clarity of the transparent conductive film is about 460 to 500% (preferably about 470 to 500%, the higher the value, the less whitish it is, and the more preferable), so that the transparent conductive film is not whitish and is clear. The method for measuring the average value of the transmitted image clarity will be described in detail in the Examples section.

[0022] <2. Transparent conductive film> The average arithmetic mean height (AVSa) of the transparent conductive film is 2 nm or more and 50 nm or less, preferably 3 nm or more and 30 nm or less, more preferably 4 nm or more and 15 nm or less. By setting AVSa within the above range, a transparent conductive film having good continuous input durability, anti-sticking property and appearance is obtained. When AVSa is large, anti-sticking property tends to improve, and when AVSa is small, continuous input durability tends to improve. Furthermore, when AVSa is small, the whitishness of the entire transparent conductive film tends to decrease and the appearance tends to improve. The AVSa has a particularly strong effect on anti-sticking property and appearance. When AVSa is large, the contact area between the transparent conductive film and the ITO glass substrate decreases, and it becomes difficult for them to stick together, improving anti-sticking property, but on the other hand, the appearance becomes whitish. Therefore, AVSa is set to the above range from the balance between anti-sticking property and appearance.

[0023] The average maximum peak height (AVSp) of the transparent conductive film is 150 nm or more and 1000 nm or less, preferably 200 nm or more and 800 nm or less, more preferably 250 nm or more and 600 nm or less. By setting AVSp within the above range, a transparent conductive film having good continuous input durability, anti-sticking property and appearance can be obtained. When AVSp is large, anti-sticking property tends to improve, and when AVSp is small, continuous input durability tends to improve. When AVSp is small, white spots caused by protrusions on the transparent conductive film become hard to see, and the appearance tends to improve. AVSp has a particularly strong effect on continuous input durability and appearance. If AVSp is too large, the protrusions on the transparent conductive film become high, so that the force received by these high protrusions increases when a continuous input test is performed on the touch panel, and the transparent conductive film becomes easily broken. This means that the conductivity of the transparent conductive film is deteriorated, which affects the continuous input durability. Also, if AVSp is too large, the protrusions become high, so that the width of the protrusions also easily spreads, and white spots become easily visible. This leads to a deterioration in appearance. From this viewpoint, the AVSp is set in the above range.

[0024] The transparent conductive film of the present invention has an average protrusion width of 12 μm or less on the transparent conductive film side surface and the surface opposite to the surface on which the transparent conductive film is laminated, as determined by the following test method 1. As a result of intensive research by the present inventors, it was found that if the average protrusion width is within the above range, white spots caused by protrusions on the transparent conductive film surface become very difficult to see, and the appearance is improved. In particular, the smaller the average protrusion width, the less likely the white spots caused by protrusions on the transparent conductive film surface become to be seen, and the appearance tends to improve. The average protrusion width is preferably 0.01 μm or more and 11 μm or less, more preferably 0.03 μm or more and 10 μm or less, and even more preferably 0.05 μm or more and 9 μm or less. [Test method 1] Particle analysis is performed using a three-dimensional surface profile measuring device, VertScan (measurement conditions: wave mode, measurement wavelength 560 nm, objective lens 50x, field of view 188.709 μm × 141.496 μm) in the following steps (i) to (v). (i) The cross-sectional area of ​​all protrusions at a height of 0.1 μm from the lowest point on the measurement surface (T c This measurement is performed on both the transparent conductive film side surface and the surface opposite to the surface on which the transparent conductive film is laminated, and the sum of the cross-sectional areas of all protrusions on the transparent conductive film side surface and the surface opposite to the surface on which the transparent conductive film is laminated is taken as the cross-sectional area of ​​all protrusions (T c ) (ii) The average cross-sectional area of ​​all protrusions (the total number of protrusions is N p Then, T c / N p ) is required. (iii) Mean value (T c / N p ) and the average value (T c / N p ) does not include protrusions with a cross-sectional area of ​​1 / 10 or less of the (iv) From the protrusions remaining in (iii), the top 20% and bottom 20% of the protrusions are further removed in order of largest cross-sectional area. (v) For the protrusions remaining in (iv), the average cross-sectional area (A) is calculated, and this value is substituted into the following formula (1) to calculate the average protrusion width (B). Formula (1): Average protrusion width (B) = 2 × (A÷π) 0.5

[0025] The transparent conductive film of the present invention has a laminate strength of 450N / 15mm or more as determined by the following test method 2. As a result of intensive research by the present inventors, it has been found that if the laminate strength of the transparent conductive film is within the above range, the transparent conductive film can be evaluated as having high adhesion to its lower layer, and the transparent conductive film is less likely to peel off, so that the continuous input durability can be improved. A higher laminate strength is desirable for continuous input durability, and the laminate strength is preferably 500N / 15mm or more, more preferably 550N / 15mm or more. On the other hand, although there is no particular upper limit set for the laminate strength, if the laminate strength is too high, the adhesive layer may be destroyed during measurement, and the laminate strength may not be measured accurately. The laminate strength is generally 2000N / 15mm or less, and may be 1500N / 15mm or less, 1000N / 15mm or less, or 800N / 15mm or less. In addition, Test Method 2 described below can adequately determine the high adhesion of a transparent conductive film compared to the adhesion test conforming to JIS K5600-5-6:1999, which is known as a general adhesion evaluation method, and therefore can be said to be a more suitable test for evaluating transparent conductive films that contribute to continuous input durability. [Test method 2] A urethane-based two-component curing adhesive (containing 4% by mass of ethyl acetate as a solvent) is applied to the transparent conductive film side surface of the transparent conductive film using wire bar #5, and then heated at 60°C for 1 minute. The adhesive-coated surface of the transparent conductive film and the PET surface of a PET film (thickness 100 μm) are then bonded together at 60°C by dry lamination (0.3 MPa, width 70 cm), and aged at 40°C for 4 days to obtain a laminate for evaluation. The obtained laminate is cut into a width of 15 mm and a length of 150 mm to prepare a test piece, and a T-peel test is performed under conditions of a temperature of 23°C, a relative humidity of 65%, and a peel speed of 100 mm / min to measure the maximum load.

[0026] The thickness of the transparent conductive film is preferably 10 nm or more and 100 nm or less, more preferably 13 nm or more and 50 nm or less, even more preferably 15 nm or more and 30 nm or less, and even more preferably 16 nm or more and 25 nm or less. When the thickness of the transparent conductive film is 10 nm or more, the entire transparent conductive film adheres to the entire transparent plastic film substrate (the cured resin layer when a cured resin layer is laminated), and the film quality of the transparent conductive film is stable, which leads to a stable surface resistance value. It is also effective in increasing the laminate strength of the transparent conductive film. On the other hand, when the thickness of the transparent conductive film is 100 nm or less, the reflection and absorption of light by the transparent conductive film is appropriate, and the total light transmittance is at a practical level. It is also preferable from the viewpoint of productivity.

[0027] The concentration of tin oxide contained in the transparent conductive film is preferably 0.5% by mass or more and 11% by mass or less, more preferably 1% by mass or more and 8% by mass or less, and even more preferably 2% by mass or more and 6% by mass or less. By containing 0.5% by mass or more of tin oxide, the surface resistance of the transparent conductive film becomes a practical level, which is preferable. Furthermore, by setting the tin oxide concentration to 11% by mass or less, the transparent conductive film becomes more likely to crystallize, and the continuous input durability and total light transmittance can be improved. Furthermore, if it is within the above range, it is also effective in increasing the laminate strength of the transparent conductive film.

[0028] The crystallinity of the transparent conductive film is preferably 70% or more, more preferably 80% or more, and even more preferably 90% or more. If the crystallinity of the transparent conductive film is 70% or more, the abrasion resistance and lamination strength of the transparent conductive film are increased, which leads to improved durability against continuous input. Furthermore, if it is within the above range, the transparency of the transparent conductive film is increased, and the total light transmittance can be improved. The higher the crystallinity, the more preferable it is, and the upper limit is 100% or less.

[0029] The static friction coefficient of the transparent conductive film is preferably 1.00 or less, more preferably 0.80 or less, and even more preferably 0.50 or less. If it is within the above range, the transparent conductive film and the fixed electrode can slide well, so that the anti-sticking property can be improved. The static friction coefficient of the transparent conductive film is preferably smaller, and is usually 0.15 or more in consideration of inexpensive production.

[0030] The dynamic friction coefficient of the transparent conductive film is preferably 0.80 or less, more preferably 0.60 or less, and even more preferably 0.50 or less. If it is within the above range, the transparent conductive film and the fixed electrode can slide well, so that the anti-sticking property can be improved. The smaller the dynamic friction coefficient of the transparent conductive film, the better, and in consideration of low-cost production, it is usually 0.15 or more.

[0031] The surface resistance of the transparent conductive film is preferably 50 Ω / □ or more and 900 Ω / □ or less, more preferably 60 Ω / □ or more and 700 Ω / □ or less, and even more preferably 70 Ω / □ or more and 500 Ω / □ or less. If the surface resistance is within the above range, the transparent conductive film is of a practical standard.

[0032] The method for forming the transparent conductive film is not particularly limited, but a preferred method is, for example, a method in which a transparent conductive film of indium-tin composite oxide is formed by sputtering on at least one surface of a transparent plastic film substrate 7 (hereinafter referred to as a film to be treated) on whose surface a cured resin layer 6 may be formed. In order to manufacture a transparent conductive film with high productivity, it is preferable to use a so-called roll-type sputtering device in which the film to be treated is supplied from a film roll and, after film formation, is wound up into a film roll shape.

[0033] Fig. 5 is a schematic diagram of an apparatus showing an example of a film formation method in a roll-type sputtering apparatus. In this illustrated example, a film 1 to be treated, fed from a film roll (not shown), runs while partially contacting the surface of a center roll 2. An indium-tin sputtering target 4 is placed in a chimney 3 having an opening toward the contact portion between the film to be treated 1 and the center roll 2, and a thin film of indium-tin composite oxide is deposited and laminated on the surface of the film to be treated 1 running on the center roll 2. The temperature of the center roll 2 can be controlled by a temperature regulator (not shown).

[0034] As the target, it is preferable to use a sintered target of indium-tin composite oxide. In order to improve production efficiency, a plurality of sintered targets of indium-tin composite oxide may be placed in the flow direction of the film.

[0035] To form the film forming atmosphere, it is preferable to flow oxygen gas, inert gas (such as argon gas), etc. while using a mass flow controller as necessary. By adding oxygen gas, the surface resistance and total light transmittance of the transparent conductive film can be made more appropriate. The flow rate ratio (volume ratio) of oxygen gas to inert gas (oxygen gas / inert gas) is, for example, 0.005 or more, preferably 0.010 or more, more preferably 0.020 or more, and, for example, 0.15 or less, preferably 0.1 or less, more preferably 0.07 or less, and even more preferably 0.05 or less. In addition, a hydrogen atom-containing gas (hydrogen, ammonia, hydrogen + argon mixed gas, etc., as long as it contains hydrogen atoms, but water is excluded) may be flowed into the film formation atmosphere using a mass flow controller as necessary.

[0036] The median value (the intermediate value between the maximum and minimum values) of the ratio of water pressure to inert gas in the film formation atmosphere (water pressure / inert gas partial pressure) is, for example, 7.00×10 -3 Less than or equal to 5.00×10 -3 Less than or equal to 3.00×10, more preferably -3The lower the water content in the film formation atmosphere, the more appropriate the film quality of the transparent conductive film, the easier it is for the surface resistance value to be a desirable value, and the more reliable the crystallization. Although it is possible to control the amount of water using the ultimate vacuum as a guide, it is preferable to measure the amount of water (water pressure) during film formation for the following two reasons. First, when a film is formed on a plastic film by sputtering, the film is heated and water is released from the film. The ultimate vacuum does not reflect the effect of this released amount of water. Second, the ultimate vacuum does not reflect the effect of the water in the center of the roll when the film is formed after being unwound from the film roll. When the film roll is held in a vacuum chamber, the water in the outer layer of the roll is easy to remove, but the water in the inner layer of the roll is difficult to remove. When the ultimate vacuum is measured, the film is stopped running, but during film formation, the film runs and the inner layer of the film roll, which contains a lot of water, is unwound, so the amount of water in the film formation atmosphere increases, and is greater than the amount of water when the ultimate vacuum is measured. The median value of the water pressure ratio (water pressure / inert gas partial pressure) is 0.3 x 10 -3 More than that is fine.

[0037] In the film roll for forming the transparent conductive film, the height difference between the most convex and most concave points on the roll end face is preferably 10 mm or less, more preferably 8 mm or less, and even more preferably 4 mm or less. If it is 10 mm or less, water and organic components are less likely to be released from the film end face when the film roll is inserted into a sputtering device, so the quality of the transparent conductive film is good. The height difference may be 1 mm or more.

[0038] Before forming the transparent conductive film, it is desirable to pass the treated film through a bombardment process. The bombardment process is a process in which a voltage is applied and discharge is performed to generate plasma while only an inert gas such as argon gas or a mixture of a reactive gas such as oxygen and an inert gas is flowing. Specifically, it is desirable to bombard the film by RF sputtering using a SUS target or the like. The bombardment process exposes the film to plasma, which releases water and organic components from the film, and reduces the amount of water and organic components released from the film when the transparent conductive film is formed, improving the quality of the transparent conductive film. In addition, the bombardment process activates the layer that the transparent conductive film comes into contact with, improving the adhesion (lamination strength) of the transparent conductive film and further improving its durability against continuous input.

[0039] A protective film with low water absorption may be attached to the surface of the film 1 opposite to the surface on which the transparent conductive film is formed. By attaching the protective film, gas such as water is less likely to be released from the film 1, and the quality of the transparent conductive film is improved. Examples of the base material for the protective film include olefins such as polyethylene, polypropylene, and cycloolefin.

[0040] During film formation, the film 1 to be treated is cooled, for example, to 0°C or lower, preferably -5°C or lower. By cooling the film 1 to be treated, it is possible to suppress the release of impurities such as water and organic gases from the film, and to ensure the quality of the transparent conductive film is appropriate. The film temperature during film formation can be substituted with the set temperature of a temperature regulator that adjusts the temperature of the center roll with which the running film comes into contact (when there are multiple set temperatures, the intermediate value between the maximum and minimum values). The film temperature may be -20°C or higher.

[0041] The sputtering apparatus is preferably equipped with an exhaust device such as a rotary pump, a turbo molecular pump, a cryopump, etc. The amount of moisture in the film formation atmosphere can be controlled by the exhaust device.

[0042] After forming and laminating a transparent conductive film of indium-tin composite oxide on the film to be treated, it is desirable to perform a heat treatment in an oxygen-containing atmosphere at 80°C or higher and 200°C or lower for 0.1 to 12 hours. By setting the temperature at 80°C or higher, the crystallinity of the transparent conductive film can be increased, and the durability against continuous input can be further improved. By setting the temperature at 200°C or lower, the flatness of the transparent plastic film can be ensured. The temperature is preferably 100°C or higher and 180°C or lower, more preferably 120°C or higher and 170°C or lower. The time is preferably 0.3 to 6 hours, more preferably 0.5 to 2 hours.

[0043] <3. Transparent plastic film substrate> The transparent plastic film substrate is a film obtained by melt-extruding or solution-extruding an organic polymer into a film shape, and then stretching the film in the longitudinal direction and / or the transverse direction, cooling, and heat setting as necessary. The transparent plastic film substrate may be a uniaxially oriented film or a biaxially oriented film.

[0044] Examples of the organic polymer include polyolefins such as polyethylene and polypropylene; polyesters such as polyethylene terephthalate, polyethylene-2,6-naphthalate, polypropylene terephthalate, and polybutylene terephthalate; polyamides such as nylon 6, nylon 4, nylon 66, and nylon 12; polyimide, polyamideimide, polyethersulfane, polyetheretherketone, polycarbonate, polyarylate, cellulose propionate, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, polyetherimide, polyphenylene sulfide, polyphenylene oxide, polystyrene, syndiotactic polystyrene, and norbornene-based polymers. Among these, polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, polyethylene-2,6-naphthalate, syndiotactic polystyrene, norbornene-based polymers, polycarbonate, and polyarylate are preferred. These organic polymers may be copolymerized with a small amount of monomers of other organic polymers, or may be blended with other organic polymers.

[0045] The transparent plastic film substrate may be subjected to a surface activation treatment such as corona discharge treatment, glow discharge treatment, flame treatment, ultraviolet irradiation treatment, electron beam irradiation treatment, or ozone treatment, as long as it does not impair the object of the present invention.

[0046] The thickness of the transparent plastic film substrate is preferably 80 μm or more and 240 μm or less, more preferably 120 μm or more and 220 μm or less. The thinner the substrate, the longer the length of the film that can be introduced into a device for forming a transparent conductive film, such as a roll-type sputtering device, and this is preferable from the viewpoint of productivity. If the substrate is 80 μm or more thick, the mechanical strength is maintained, so that when used in a touch panel, deformation due to input with a pen or the like is small, and durability to continuous input is excellent, which is preferable. If the thickness is 240 μm or less, it is preferable because input can be performed with a light force when used in a touch panel.

[0047] <4.Curing resin layer> The resin constituting the curable resin layer may be any resin that is cured by application of energy such as heating, ultraviolet irradiation, or electron beam irradiation, or by a curing agent, and examples of such resins include silicone-based resins, (meth)acrylic-based resins, epoxy-based resins, melamine-based resins, polyester-based resins, and urethane-based resins. These may be used alone or in combination of two or more. From the viewpoint of productivity, it is preferable that the resin constituting the curable resin layer is an ultraviolet-curable resin.

[0048] Examples of ultraviolet-curable resins include polyfunctional (meth)acrylate resins such as acrylic acid esters or methacrylic acid esters of polyhydric alcohols, and polyfunctional urethane (meth)acrylate resins synthesized from diisocyanates, polyhydric alcohols, and hydroxyalkyl esters of acrylic acid or methacrylic acid, etc. These polyfunctional resins may be copolymerized with monofunctional monomers such as vinylpyrrolidone, methyl methacrylate, and styrene, as necessary.

[0049] The curable resin layer may contain a resin that is not compatible with the resin (hereinafter, may be simply referred to as an incompatible resin) in addition to the resin that constitutes the curable resin layer described above (i.e., the resin that is the main component that constitutes the curable resin layer). By dispersing the incompatible resin in the curable resin layer, it is possible to form appropriate unevenness on the surface of the curable resin layer, and to increase the surface roughness over a wide area. Examples of the incompatible resin include polyester resins, polyolefin resins, polystyrene resins, and polyamide resins.

[0050] The curable resin layer preferably further contains particles. The particles can form appropriate unevenness on the surface of the curable resin layer and the transparent conductive film adjacent thereto. This means that the AVSa and AVSp of the transparent conductive film can be controlled within a predetermined range. When the curable resin layer contains particles, unevenness is formed on the transparent conductive film due to the unevenness of the surface of the curable resin layer. For example, in a resistive touch panel, when the transparent conductive film and the fixed electrode come into contact with each other, a gap is formed between the fixed electrode and the transparent conductive film due to the unevenness of the transparent conductive film, thereby suppressing adhesion (sticking) between the transparent conductive film and the fixed electrode. Since sticking can cause a malfunction of the touch panel, it is essential in this field to prevent sticking. In addition, when the curable resin layer contains particles, it is also possible to improve continuous input durability, anti-Newton ring properties, film winding properties, etc.

[0051] The particles contained in the curable resin layer include at least one selected from inorganic particles and organic particles. Examples of inorganic particles include silica particles. Examples of organic particles include particles made of polyester resin, polyolefin resin, polystyrene resin, polyamide resin, acrylic resin, etc. These may be used alone or in combination of two or more.

[0052] The particles may be either monodisperse or polydisperse, with monodisperse being particularly preferred.

[0053] A preferred embodiment of the curable resin layer is one that contains particles (A) having a number average particle diameter of 1.0 μm or more and 6.5 μm or less. Another preferred embodiment of the curable resin layer is one that contains particles (B) having a number average particle diameter of 0.01 μm or more and less than 1.0 μm. Another preferred embodiment of the curable resin layer is one that contains particles (A) having a number average particle diameter of 1.0 μm or more and 6.5 μm or less and particles (B) having a number average particle diameter of 0.01 μm or more and less than 1.0 μm. Each of the particles (A) and the particles (B) may be used alone or in combination of two or more.

[0054] The number average particle diameter of the particles (A) is more preferably 2.0 μm or more and 5.5 μm or less, and even more preferably 2.8 μm or more and 5.0 μm or less. The number average particle diameter of the particles (B) is more preferably 0.06 μm or more and 0.5 μm or less, and even more preferably 0.1 μm or more and 0.4 μm or less. When the number average particle diameter is large, the unevenness of the transparent conductive film becomes large, and as a result, the AVSa and AVSp of the transparent conductive film become large, and the sticking resistance is improved. When the number average particle diameter is small, the unevenness of the transparent conductive film becomes small, and as a result, the AVSa and AVSp of the transparent conductive film become small, and the continuous input durability is improved. In addition, when the number average particle diameter is small, the average protrusion width tends to become small. As a result, the whitishness of the entire surface of the curable resin layer disappears, and the white spots caused by the protrusions of the curable resin layer become less visible, resulting in a good appearance.

[0055] The standard deviation of the particle diameter of the particles (A) and the particles (B) is preferably 20% or less of the number average particle diameter, more preferably 10% or less of the number average particle diameter, and even more preferably 5% or less of the number average particle diameter. The smaller the standard deviation of the particle diameter, the more uniform the height of the unevenness of the curable resin layer, so that stable sticking resistance and durability to continuous input can be realized. Furthermore, uniformity of the height of the unevenness of the curable resin layer can reduce the frequency of occurrence of white spots caused by protrusions on the curable resin layer, resulting in a good appearance.

[0056] The number average particle diameter of the particles (A) is preferably slightly smaller than or equal to the thickness of the curable resin layer. By adjusting the balance between the number average particle diameter of the particles (A) and the thickness of the curable resin layer, AVSa and AVSp can be easily controlled. The number average particle diameter of the particles (A) is preferably 0.7 to 1.5 times the thickness of the curable resin layer, more preferably 0.8 to 1.4 times, and even more preferably 0.9 to 1.3 times. If it is 0.7 times or more, it is easy to form appropriate unevenness in the curable resin layer, and the winding property of the film is also improved. If it is 1.5 times or less, the falling off of the particles can be suppressed even if a strong load is applied. Note that when the number average particle diameter of the particles (A) is sufficiently large compared to the thickness of the curable resin layer, AVSa, AVSp, and the average projection width may become too large. In this case, AVSa, AVSp, and the average projection width can be reduced by reducing the number average particle diameter of the particles (A) or reducing the amount of the particles (A) added. On the other hand, when the number average particle diameter of the particles (A) is sufficiently small relative to the thickness of the curable resin layer, AVSa and AVSp may become too small. In this case, AVSa and AVSp can be increased by increasing the number average particle diameter of the particles (A), etc.

[0057] When the curable resin layer contains particles (A), the particles (A) are preferably contained in an amount of 0.1% by mass to 30% by mass, more preferably 2.5% by mass to 20% by mass, and even more preferably 5% by mass to 15% by mass, based on 100% by mass of the solid content constituting the curable resin layer. The AVSa of the transparent conductive film tends to increase as the amount of particles (A) increases.

[0058] When the curable resin layer contains particles (B), the particles (B) are preferably contained in an amount of 0.05% by mass to 25% by mass, more preferably 0.1% by mass to 22% by mass, and even more preferably 0.5% by mass to 18% by mass, based on 100% by mass of the solid content constituting the curable resin layer. As the amount of particles (B) increases, the unevenness of the curable resin layer increases, and as a result, the AVSa and AVSp of the transparent conductive film also increase, improving the sticking resistance of the transparent conductive film.

[0059] Furthermore, when the curable resin layer contains both particles (A) and particles (B), when the total content of particles (A) and particles (B) is taken as 100 mass%, the content of particles (B) is preferably 0.1 mass% or more and 99.9 mass% or less, more preferably 20 mass% or more and 80 mass% or less, and even more preferably 30 mass% or more and 70 mass% or less.

[0060] The particles (A) may be either inorganic or organic particles, but are preferably organic particles, and more preferably particles made of an acrylic resin. The particles (B) may be either inorganic or organic particles, but are preferably inorganic particles, and more preferably silica particles.

[0061] The thickness of the curable resin layer is preferably 0.8 μm or more and 6.2 μm or less, more preferably 1.0 μm or more and 5.0 μm or less, and even more preferably 2.0 μm or more and 4.0 μm or less. If the thickness of the curable resin layer is 0.8 μm or more, even if the curable resin layer contains particles, the particles can be prevented from falling off while forming sufficient protrusions. On the other hand, if the thickness of the curable resin layer is 6.2 μm or less, the productivity is good. Note that if the curable resin layer is thick, AVSa, AVSp and average protrusion width tend to decrease.

[0062] The curable resin layer is formed by preparing a liquid composition for a curable resin layer containing a resin capable of forming a curable resin layer, applying the composition for a curable resin layer to an object to be laminated (e.g., a transparent plastic film substrate, an easily adhesive layer, etc.), and then curing the resin.

[0063] The composition for the curable resin layer may further contain, in addition to the resin capable of forming the curable resin layer described above, an incompatible resin, particles, a curing reaction initiator, a solvent, various known additives, and the like.

[0064] The curing reaction initiator can be selected according to the type of curing of the resin constituting the curable resin layer, and examples thereof include radical polymerization initiators such as thermal polymerization initiators and photopolymerization initiators, various curing agents, and the like, among which photopolymerization initiators are preferred. As the photopolymerization initiator, a known initiator that absorbs ultraviolet light to generate radicals can be appropriately used, and examples thereof include benzoins, phenyl ketones, and benzophenones. The content of the curing reaction initiator is preferably 1 part by mass or more and 5 parts by mass or less relative to 100 parts by mass of the resin.

[0065] The solvent used in the curable resin layer composition is not particularly limited, and examples thereof include alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, ester-based solvents such as ethyl acetate and butyl acetate, ether-based solvents such as dibutyl ether and ethylene glycol monoethyl ether, ketone-based solvents such as methyl ethyl ketone, methyl isobutyl ketone and cyclohexanone, and aromatic hydrocarbon-based solvents such as toluene, xylene and solvent naphtha. These may be used alone or in combination of two or more.

[0066] As various additives used in the curable resin layer composition, a leveling agent is preferably used. Since the leveling agent can suppress unevenness and defects, the entire surface of the curable resin layer can be made clear. In addition, when protrusions are present in the curable resin layer, the leveling agent can suppress the spreading of the bottom of the protrusions, which is preferable because the white spots caused by the protrusions are less visible. The amount of the leveling agent is preferably 0.01 parts by mass or more and 0.55 parts by mass or less, more preferably 0.02 parts by mass or more and 0.45 parts by mass or less, and even more preferably 0.03 parts by mass or more and 0.35 parts by mass or less, relative to 100 parts by mass of the resin. When the amount of the leveling agent is increased, unevenness and defects are easily suppressed, and when protrusions are present in the curable resin layer, the spreading of the bottom of the protrusions is easily suppressed (the average protrusion width can be reduced), which is preferable. On the other hand, when the amount of the leveling agent is decreased, the adhesion between the transparent conductive film and the curable resin layer is not hindered, and it is expected that the laminate strength will increase. Examples of the leveling agent include silicone-based leveling agents, fluorine-based leveling agents, acrylic-based leveling agents, vinyl-based leveling agents, etc., and among these, silicone-based leveling agents are preferred. These may be used alone or in combination of two or more.

[0067] The solid content of the composition for the curable resin layer may be appropriately adjusted so as to have a suitable viscosity according to the coating method. The solid content is preferably 30% by mass or more and 75% by mass or less, more preferably 35% by mass or more and 65% by mass or less, and even more preferably 40% by mass or more and 55% by mass or less. In general, the higher the solid content, the larger the AVSa, AVSp, and average projection width tend to be.

[0068] The method of coating the liquid curable resin layer composition on the laminated object is not particularly limited, and known methods such as bar coating, gravure coating, and reverse coating can be appropriately used. The coated curable resin layer composition is then subjected to a drying step in which the solvent is evaporated and removed. If an incompatible resin (e.g., polyester resin) is dissolved in the curable resin layer composition, the incompatible resin becomes particles and precipitates in the composition in the drying step. After the drying step, a curable resin layer is formed by carrying out an appropriate treatment (e.g., ultraviolet irradiation) according to the type of curing.

[0069] Furthermore, the surface of the laminate to which the composition for a curable resin layer is applied may be treated to improve the adhesion of the curable resin layer before application, if necessary. Examples of the treatment to improve the adhesion include a discharge treatment method in which glow or corona discharge is applied to increase carbonyl groups, carboxyl groups, and hydroxyl groups, and a chemical treatment method in which acid or alkali is used to increase polar groups such as amino groups, hydroxyl groups, and carbonyl groups.

[0070] <5. Functional layer> The resin constituting the functional layer is exemplified by the same resin as that constituting the curable resin layer described above, and from the viewpoint of productivity, the resin constituting the functional layer is preferably an ultraviolet curable resin.Specific examples of the ultraviolet curable resin are the same as those exemplified in the section on the resin constituting the curable resin layer.Furthermore, the functional layer may contain an incompatible resin, similar to the curable resin layer.

[0071] The functional layer preferably further contains particles, which can provide the functional layer with smooth input characteristics that prevent fingers from getting caught, and also make it easier to wind up the transparent conductive film.

[0072] The particles contained in the functional layer include at least one selected from inorganic particles and organic particles. Examples of inorganic particles include silica particles. Examples of organic particles include particles made of polyester resin, polyolefin resin, polystyrene resin, polyamide resin, acrylic resin, etc. These may be used alone or in combination of two or more. The particles contained in the functional layer and the particles contained in the curable resin layer may be of the same or different nature. The particles contained in the functional layer may be either monodisperse or polydisperse.

[0073] A preferred embodiment of the functional layer includes particles (C) having a number-average particle diameter of 0.01 μm or more and 0.5 μm or less. The number-average particle diameter of the particles (C) is more preferably 0.02 μm or more and 0.3 μm or less, and even more preferably 0.03 μm or more and 0.2 μm or less. If the number-average particle diameter is 0.5 μm or less, the functional layer tends to have a good appearance. If the number-average particle diameter is 0.01 μm or more, the functional layer tends to have good finger sliding properties. The particles (C) may be used alone or in combination of two or more types. The standard deviation of the particle diameter of the particles (C) is preferably 20% or less of the number-average particle diameter, more preferably 10% or less of the number-average particle diameter, and even more preferably 5% or less of the number-average particle diameter.

[0074] When the functional layer contains particles (C), the particles (C) are preferably contained in an amount of 0.1% by mass to 50% by mass, more preferably 0.3% by mass to 30% by mass, and even more preferably 0.5% by mass to 20% by mass, based on 100% by mass of the solid content constituting the functional layer. The finger slipperiness of the transparent conductive film can be adjusted by the amount of particles (C). In addition, the particles (C) can form protrusions on the surface of the functional layer, making it easier to wind up the film.

[0075] The thickness of the functional layer is preferably 0.8 μm to 8.0 μm, more preferably 1.0 μm to 6.5 μm, and even more preferably 2.0 μm to 5.0 μm. If the thickness of the functional layer is 0.8 μm or more, the transparent conductive film can be provided with smooth input properties that do not catch fingers and with prevention of scratches when inputting with a pen or the like. If the thickness of the functional layer is 8.0 μm or less, the productivity is good.

[0076] The static friction coefficient of the functional layer is preferably 0.70 or less, more preferably 0.50 or less, even more preferably 0.40 or less, and even more preferably 0.30 or less. If it is within the above range, the functional layer and the finger can slide well, so that when the finger inputs on the touch panel, the input is smooth and does not get caught. The static friction coefficient of the functional layer is preferably smaller, and is usually 0.15 or more in consideration of low-cost production.

[0077] The dynamic friction coefficient of the functional layer is preferably 0.50 or less, more preferably 0.40 or less, and even more preferably 0.35 or less. If it is within the above range, the functional layer and the finger can slide well, so that when the finger inputs on the touch panel, the input is smooth and does not get caught. The dynamic friction coefficient of the functional layer is preferably smaller, and is usually 0.15 or more in consideration of low-cost production.

[0078] The functional layer is formed by preparing a liquid composition for functional layer containing a resin capable of forming a functional layer, applying the composition for functional layer to a laminated object (for example, a transparent plastic film substrate, an easy-adhesion layer, etc.), and then curing the resin, in the same manner as the curable resin layer. In addition to the resin capable of forming a functional layer, the composition for functional layer may further contain an incompatible resin, particles, a curing reaction initiator, a solvent, various known additives, etc. The curing reaction initiator, the solvent, the various known additives, and the method of coating the liquid composition for functional layer on the laminated object are appropriately described in the curable resin layer. In addition, the surface to which the composition for functional layer is applied in the laminated object may be treated to improve the adhesion of the functional layer as necessary before application, and the adhesion improvement treatment is also appropriately described in the curable resin layer.

[0079] The solid content of the composition for the functional layer may be appropriately adjusted so as to have a suitable viscosity according to the coating method. The solid content is preferably 30% by mass or more and 75% by mass or less, more preferably 35% by mass or more and 65% by mass or less, and even more preferably 40% by mass or more and 55% by mass or less.

[0080] In an adhesion test according to JIS K5600-5-6:1999, the remaining area ratio of the functional layer is preferably 95% or more, more preferably 99% or more, and even more preferably 99.5% or more. If the remaining area ratio of the functional layer is within the above range, the transparent plastic film substrate and the functional layer are firmly adhered to each other, and even if continuous input is made with a pen, the functional layer is prevented from suffering from defects in appearance such as cracks, peeling, and wear. In addition, even if a force stronger than expected is applied, cracks, peeling, and the like of the functional layer are prevented, which is preferable.

[0081] <6. Easy adhesion layer> The easy-adhesion layer is preferably formed from a composition containing a urethane resin, a polyester resin, and a crosslinking agent. The crosslinking agent is preferably a blocked isocyanate, more preferably a trifunctional or higher blocked isocyanate, and even more preferably a tetrafunctional or higher blocked isocyanate. The thickness of the easy-adhesion layer is, for example, 0.001 μm or more and 2.00 μm or less. EXAMPLES

[0082] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Various measurements and evaluations in the examples were performed according to the following methods.

[0083] 1. Measurement and evaluation methods (1) Number-average particle size of particles Three observation points were randomly selected from each cross section of the curable resin layer or functional layer of the transparent conductive film, and particles at each observation point were observed using a scanning electron microscope (Keyence Corporation, VE-8800). 50 particles were randomly selected from each observation point and their particle diameters were measured. Next, for the 50 particles observed, the particle diameters (circle equivalent diameters) were divided into 0.020 μm intervals, the total number of particles contained in each interval was calculated, and a histogram was created with the number of particles on the vertical axis and particle diameters in 0.020 μm intervals on the horizontal axis. For particles with particle diameters within ±30% of the absolute value of the center value of the particle diameter interval that takes the maximum value of the normal distribution peak from the histogram, the number average of the observed particle diameters was taken as the average particle diameter. For example, if there are two normal distribution peaks in the histogram, this indicates that two types of particles have been added, and the average particle diameters of the two types were calculated using the same method as above. The average particle diameters at three points in the curable resin layer were further averaged to obtain the number average particle diameter of the curable resin layer, and the average particle diameters at three points in the functional layer were further averaged to obtain the number average particle diameter of the functional layer.

[0084] (2) Thickness of the curable resin layer and the functional layer The thickness of each layer was measured by observing the cross section of the transparent conductive film at any five points (magnification: 5000x) using a scanning electron microscope (VE-8800, manufactured by Keyence Corporation), and the average value of the thicknesses measured at the five points was recorded as the thickness of each layer.

[0085] (3) Static and dynamic friction coefficients The static and dynamic friction coefficients of the transparent conductive film surface and the functional layer surface were evaluated under the following conditions in accordance with JIS C2151. The size of the test piece was 70 mm wide x 200 mm long, the test speed was 200 mm / min, the weight of the sliding piece was 4.4 kg, and the contact area between the sliding piece and the transparent conductive film surface or the functional layer surface was 5000 mm. 2 It was.

[0086] (4) Transparent conductive film thickness A film sample piece laminated with a transparent conductive film was cut into a size of 1 mm x 10 mm and embedded in epoxy resin for electron microscopes. The epoxy resin was composed of the main agent (trade name: Epon812) (Nacalai Tesque, Inc.), the hardener (trade name: MNA) (Nacalai Tesque, Inc.), and the accelerator (trade name: DNP-30) (Nacalai Tesque, Inc.), and was mixed in a volume ratio of main agent:hardener:accelerator = 100:89:1.5 and cured at 60 °C for 12 hours. The sample piece encapsulated in the epoxy resin was fixed to the sample holder of an ultramicrotome, and a cross-sectional thin section parallel to the short side of the embedded sample piece was prepared. Next, a transmission electron microscope (JEOL, JEM-2010) was used to photograph a part of the thin film of the slice that was not significantly damaged, at an accelerating voltage of 200 kV, in a bright field, and a magnification of 10,000 times, and the film thickness was determined from the photograph obtained.

[0087] (5) Tin oxide concentration in the transparent conductive film Cut a piece of transparent conductive film (approximately 15 cm 2 ) into a quartz Erlenmeyer flask, 20 ml of 6 mol / l hydrochloric acid was added, and the flask was sealed with film to prevent the acid from volatilizing. The flask was left at room temperature for 9 days with occasional shaking to dissolve the transparent conductive film. The remaining film was removed, and the hydrochloric acid in which the transparent conductive film had dissolved was used as the measurement solution. The In and Sn in the solution were determined by the calibration curve method using an ICP emission spectrometer (manufacturer: Rigaku, model: CIROS-120 EOP). The measurement wavelength for each element was selected to be one with no interference and high sensitivity. The standard solutions were also prepared by diluting commercially available standard solutions of In and Sn.

[0088] (6) Crystallinity of transparent conductive film A transparent conductive film sample piece with a laminated transparent conductive film was cut into a size of 1 mm x 10 mm and attached to the top surface of a suitable resin block with the transparent conductive film facing outward. The resin block was composed of the main agent (trade name: Epon812) (Nacalai Tesque, Inc.), the hardener (trade name: MNA) (Nacalai Tesque, Inc.), and the accelerator (trade name: DNP-30) (Nacalai Tesque, Inc.), which were mixed in a volume ratio of main agent:hardener:accelerator = 100:89:1.5 and cured at 60°C for 12 hours. After trimming the sample piece attached to the resin block, ultrathin slices were prepared almost parallel to the film surface by a general ultramicrotome technique. The slices were observed with a transmission electron microscope (JEOL, JEM-2010) to select the surface of the conductive thin film that was not significantly damaged, and photographed at an accelerating voltage of 200 kV and a direct magnification of 40,000 times. The crystallinity of the transparent conductive film was evaluated by observing the proportion of crystal grains under a transmission electron microscope, that is, the degree of crystallinity.

[0089] (7) Surface resistance The measurement was performed by the four-terminal method in accordance with JIS K7194:1994. The measurement device used was Lotesta AX MCP-T370 manufactured by Mitsubishi Chemical Analytech Co., Ltd.

[0090] (8) Adhesion test of functional layer The adhesion test of the functional layer was carried out in accordance with JIS K5600-5-6:1999. The test results of adhesion are shown as the remaining area ratio (%). The maximum remaining area ratio (%) is 100%, and the closer the remaining area ratio is to 100%, the smaller the peeled area is.

[0091] (9) Average arithmetic mean height (AVSa), average maximum peak height (AVSp) Five measurement points were selected from the transparent conductive film surface, and the arithmetic mean height (Sa) and maximum peak height (Sp) (ISO; surface roughness) were measured at each measurement point. The arithmetic mean values ​​of the five points were then evaluated as the average arithmetic mean height (AVSa) and average maximum peak height (AVSp), respectively. The five points were selected as follows. First, an arbitrary point (K) was selected. Next, in the longitudinal (MD) direction of the film, one point was selected at a position 5 cm upstream and downstream from point (K), for a total of two points. Next, in the transverse (TD) direction of the film, one point was selected at a position 5 cm left and right from point (K), for a total of two points. The measurements were performed using a 3D surface profiler, Bertscan (Ryoka Systems, R5500H-M100 (measurement conditions: wave mode, measurement wavelength 560 nm, 10x objective lens for AVSa measurement, 110x objective lens for AVSp measurement)) in accordance with ISO 25178 to determine the arithmetic mean height (Sa) and maximum peak height (Sp) (ISO; surface roughness). Values ​​less than 1 nm were rounded off.

[0092] (10) Average protrusion width The average projection width is determined by Test Method 1 below. [Test method 1] Particle analysis is performed using a three-dimensional surface profile measuring device, Bertscan (R5500H-M100, manufactured by Ryoka Systems, measurement conditions: wave mode, measurement wavelength 560 nm, objective lens 50x, field of view 188.709 μm × 141.496 μm) in the following steps (i) to (v). (i) The cross-sectional area of ​​all protrusions at a height of 0.1 μm from the lowest point on the measurement surface (T c This measurement is performed on both the transparent conductive film side surface and the surface opposite to the surface on which the transparent conductive film is laminated, and the sum of the cross-sectional areas of all protrusions on the transparent conductive film side surface and the surface opposite to the surface on which the transparent conductive film is laminated is taken as the cross-sectional area of ​​all protrusions (T c ) (ii) The average cross-sectional area of ​​all protrusions (the total number of protrusions is N p Then, T c / N p ) is required. (iii) Mean value (T c / N p) and the average value (T c / N p ) does not include protrusions with a cross-sectional area of ​​1 / 10 or less of the (iv) From the protrusions remaining in (iii), the top 20% and bottom 20% of the protrusions are further removed in order of largest cross-sectional area. (v) For the protrusions remaining in (iv), the average cross-sectional area (A) is calculated, and this value is substituted into the following formula (1) to calculate the average protrusion width (B). Formula (1): Average protrusion width (B) = 2 × (A÷π) 0.5

[0093] (11) Lamination strength of transparent conductive film The laminate strength of the transparent conductive film is determined by the following Test Method 2. [Test method 2] A urethane-based two-component curing adhesive (containing 4% by mass of ethyl acetate as a solvent; Takelac (registered trademark) A525S (manufactured by Mitsui Chemicals), Takenate (registered trademark) A50 (manufactured by Mitsui Chemicals), and ethyl acetate (Nacalai Tesque) in a ratio of 13.5:8.2:1 (mass ratio)) is applied to the transparent conductive film side surface of the transparent conductive film with a wire bar #5, and then heated at 60°C for 1 minute. Thereafter, the adhesive-coated surface of the transparent conductive film and the PET surface (flat surface side of the uneven surface and flat surface) of a PET film (Cosmoshine (registered trademark) A4160, manufactured by Toyobo Co., Ltd., thickness 100 μm) are bonded together at 60°C by a dry lamination method (0.3 MPa, width 70 cm), and aging is performed at 40°C for 4 days to obtain a laminated laminate for evaluation. The thickness of the adhesive layer formed from the urethane-based two-component curing adhesive after drying was about 4 μm. The obtained laminated body is cut into a test piece having a width of 15 mm and a length of 150 mm, and a T-peel test is performed using an autograph (Shimadzu Corporation's "Autograph AG-X") under conditions of a temperature of 23°C, a relative humidity of 65%, and a peel speed of 100 mm / min, to measure the maximum load.

[0094] (12) Continuous input durability The continuous input durability of the transparent conductive film was evaluated by the following Test Method 3. [Test method 3] A glass substrate (size: 60 mm × 50 mm) was placed in a sputtering device and then 1.5 × 10 -4 The chamber was evacuated to a vacuum of 10 mPa. Oxygen was then introduced to 10 mPa, and argon was then introduced to bring the total pressure to 0.6 Pa. An indium-tin composite oxide sintered target (tin oxide content: 10% by mass, manufactured by Mitsui Mining & Smelting Co., Ltd.) was used, and the sintering pressure was 3 W / cm. 2A power density of 10 ... The ITO glass substrate and the transparent conductive film of the obtained evaluation panel were connected to a constant voltage power supply, and 5V was applied. Next, a load of 2.5N was applied to a polyacetal pen (trade name "TPS (registered trademark) POM (NC)", manufactured by Toray Plastics Precision Co., Ltd., tip shape: 0.8mmR) and a set number of area sliding tests were performed on the touch panel. The area sliding test was a set number of linear sliding tests, with a sliding distance of 30mm, a sliding speed of 180mm / sec, and 11 linear sliding tests in parallel at 0.5mm intervals. The sliding location was near the center of the evaluation panel. After the area sliding test, the constant voltage power supply was turned off, and the ITO glass substrate and the transparent conductive film of the evaluation panel were connected with a tester. Next, the resistance value was measured when the center of the area sliding part was pressed with a load of 0.5N using silicone rubber (hardness 30° in JIS K6253 durometer type A, tip shape: 120mmR). If the resistance value at this time is 4 kΩ or less, the set number of area sliding tests is deemed to be OK. After that, the set number of area sliding tests is increased and measurements are continued, and the maximum set number of area sliding tests at which the resistance value is 4 kΩ or less is evaluated as the continuous input durability of the transparent conductive film.

[0095] (13) Anti-sticking The sticking resistance of the transparent conductive film was evaluated by the following Test Method 4. [Test method 4] A pseudo-resistive touch panel was fabricated using a transparent conductive film. Specifically, a glass substrate (size: 232 mm × 151 mm) was first placed in a sputtering device, and then a 1.5 × 10 -4 The chamber was evacuated to a vacuum of 10 mPa. Oxygen was then introduced to 10 mPa, and argon was then introduced to bring the total pressure to 0.6 Pa. An indium-tin composite oxide sintered target (tin oxide content: 10% by mass, manufactured by Mitsui Mining & Smelting Co., Ltd.) was used, and the sintering pressure was 3 W / cm. 2A power density of 10 ... A transparent conductive film (size: 220mm x 135mm) was attached to a rectangular frame (double-sided tape) attached to an ITO glass substrate without applying tension, and the conductive films were laminated so that they faced each other. At this time, one short side of the transparent conductive film was made to protrude from the ITO glass substrate. Next, a polyacetal pen (trade name "TPS (registered trademark) POM (NC)", manufactured by Toray Plastics Seiko Co., Ltd., tip shape: 0.8mmR) was held in the hand, and the center of the touch panel was rubbed in a straight line about 100mm back and forth 10 times with a load of about 200g and a speed of about 10cm / sec. The sound when rubbing was confirmed. If only the sound of the pen and the transparent conductive film rubbing was heard, the sticking resistance was evaluated as OK, and if in addition to the sound of the pen and the transparent conductive film rubbing, another sound (e.g., a high-pitched popping sound) was heard between the transparent conductive film and the ITO glass, the sticking resistance was evaluated as NG. This test makes use of the phenomenon in which sound is generated between a transparent conductive film and ITO glass when the two are attached to each other.Whether any other sounds are generated besides the sound of the pen rubbing against the transparent conductive film can be determined by comparing the sound made when a pen is similarly slid across a transparent conductive film that is not attached to ITO glass.

[0096] (14) Appearance The appearance of the transparent conductive film was evaluated by the following Test Method 5. [Test method 5] The appearance of the transparent conductive film is judged by placing it under fluorescent lights of three wavelengths. The judging is based on the following three points. The first point is the evaluation of the uniformity over the entire surface of the transparent conductive film. In the evaluation of the transmission image clarity described below, the sum of the transmission image clarity at any five points and the average value (Ac) of the sum of the transmission image clarity were calculated. If the sum of the transmission image clarity at each of the five points was all within ±20% of the average value (Ac) of the sum of the transmission image clarity, the entire surface was evaluated as uniform (OK), and if even one of the sums of the transmission image clarity at each of the five points exceeded ±20% of the average value (Ac) of the sum of the transmission image clarity, the entire surface was evaluated as not uniform (NG). The second point was visual confirmation of the presence or absence of white spots on the transparent conductive film. If there were no white spots, it was rated as OK, and if there were white spots, it was rated as NG. Normally, if the average protrusion width is 12 μm or less, it is difficult to visually confirm white spots. The third point is the evaluation of the transmitted image clarity of the transparent conductive film. First, in accordance with JIS K7374, the transmitted image clarity was measured with an image clarity measuring device using five types of optical combs with a width of 0.125 mm, 0.25 mm, 0.5 mm, 1 mm, or 2 mm, and the sum of the transmitted image clarity measured with the five types of optical combs was calculated. Similarly, the transmitted image clarity was measured at five arbitrary points, and the sum of the transmitted image clarity at each point was calculated. The sum of the transmitted image clarity at the five points obtained was added up and divided by 5 to calculate the average value (Ac) of the sum of the transmitted image clarity, and a value of 460% or more was deemed to be acceptable.

[0097] (15) Total light transmittance The total light transmittance of the transparent conductive film was measured using NDH-2000 manufactured by Nippon Denshoku Industries Co., Ltd. in accordance with JIS K7361-1:1997.

[0098] 2.Laminated film In the examples, the following laminated films were used, each of which was composed of a transparent plastic film substrate, a curable resin layer, and a functional layer.

[0099] (1) Base material Substrate 1 (transparent plastic film substrate): biaxially oriented transparent PET film having an easy-adhesion layer on both sides (Toyobo Co., Ltd., Cosmoshine (registered trademark) A4380, thickness is shown in Table 1) Substrate 2 (transparent plastic film substrate): biaxially oriented transparent PET film having an easy-adhesion layer on one side and no easy-adhesion layer on the other side (Toyobo Co., Ltd., Cosmoshine (registered trademark) A4180, thickness is shown in Table 1) Substrate 3 (transparent plastic film substrate): Biaxially oriented PET film without easy-adhesion layers on both sides (manufactured by Toyobo Co., Ltd., Cosmoshine (registered trademark) A4180, the easy-adhesion layer of which was removed by wiping with Bemcot (registered trademark, manufactured by Asahi Kasei Co., Ltd.) soaked in methyl ethyl ketone, the thickness is shown in Table 1)

[0100] [Table 1]

[0101] (2) Curing resin layer Particles (particles A, particles B) having the number-average particle size shown in Table 2 and a leveling agent (silicone-based leveling agent, Dow Chemical Company, DOWSIL (registered trademark) 57 Additive) were mixed in the amounts shown in Table 2 with 100 parts by mass of a photopolymerization initiator-containing acrylic resin (Dainichi Seika Chemical Industry Co., Ltd., Seikabeam (registered trademark) EXF-01J). Particles A are monodispersed acrylic particles or polydispersed acrylic particles, and particles B are monodispersed silica particles. In Table 2, the leveling agent concentration refers to the concentration relative to 100 parts by mass of resin. Then, a mixed solvent of toluene / methyl ethyl ketone (MEK) (8 / 2: mass ratio) was added so that the solid concentration was the value shown in Table 2, and the mixture was stirred and dissolved uniformly to prepare a coating solution (coating solution A). Coating solution A, which had been adjusted to have a coating thickness of the value shown in Table 2, was applied to one side of a transparent plastic film substrate using a Mayer bar. After drying at 80°C for 1 minute, the sample was irradiated with ultraviolet light (light intensity: 300 mJ / cm) using an ultraviolet irradiation device (I-Graphics, UB042-5AM-W type). 2 ) and the coating was cured.

[0102] [Table 2]

[0103] (3) Functional layer Particles (particles C) having a number-average particle size as shown in Table 3 and a leveling agent (silicone-based leveling agent, Dow Chemical Company, DOWSIL (registered trademark) 57 Additive) were mixed in the amounts shown in Table 3 with 100 parts by mass of a photopolymerization initiator-containing acrylic resin (Dainichi Seika Chemical Industry Co., Ltd., Seikabeam (registered trademark) EXF-01J). In Table 3, the concentration of the leveling agent refers to the concentration relative to 100 parts by mass of the resin. Then, a mixed solvent of toluene / MEK (8 / 2: mass ratio) was added so that the solid content concentration was the value in Table 3, and the mixture was stirred and dissolved uniformly to prepare a coating liquid (coating liquid C). The coating liquid C, which had been adjusted to have a coating thickness of the value in Table 3, was applied to the opposite side of the curable resin layer of the transparent plastic film substrate using a Mayer bar. After drying at 80°C for 1 minute, ultraviolet light was irradiated (light amount: 300 mJ / cm) using an ultraviolet light irradiation device (I-Graphics Co., Ltd., UB042-5AM-W type). 2 ) and the coating was cured.

[0104] [Table 3]

[0105] Examples 1 to 7 Put the laminated film into the vacuum chamber and 1.5 x 10 -4 The chamber was then evacuated to a vacuum of 0.6 Pa. Next, oxygen was introduced, followed by argon, until the total pressure reached 0.6 Pa. The flow rate ratio of oxygen to argon is shown in Table 4.

[0106] As shown in Fig. 5, a transparent conductive film was formed by sputtering from a target 4 in a chimney 3 onto a curable resin layer of a laminated film (film to be treated) 1 on a center roll 2. A sintered target of indium-tin composite oxide (tin oxide concentration is shown in Table 4, the remainder being indium oxide) was used as the target 4, and the sputtering power was 3 W / cm2 A transparent conductive film was formed by DC magnetron sputtering at 1000 K. The film thickness was controlled by changing the speed at which the laminated film (film to be treated) 1 passed over the target 4. The ratio of water vapor pressure to argon in the film formation atmosphere during sputtering was measured using a gas analyzer (Transpector XPR, manufactured by Inficon), and is shown in Table 4. As shown in Table 4, the ratio of water vapor pressure was adjusted by adjusting the presence or absence of a bombardment process, the presence or absence of a protective film, the unevenness height difference on the end surface of the film roll, the temperature of the heating medium of the temperature regulator that controls the temperature of the center roll with which the film runs in contact, and the like. In the bombardment process, SUS (stainless steel) was used as the target, and 0.5 W / cm 2 The amount of gas introduced in the RF sputtering was the same as the amount of gas introduced into the vacuum apparatus described in the Examples. When a protective film was used, a polyethylene film having a thickness of 65 μm was used as the protective film. An acrylic adhesive was applied to one side of the protective film, and the protective film was attached to the side of the laminate film opposite to the side on which the transparent conductive film was formed. The temperature of the hot medium is shown in Table 4 as the temperature exactly in the middle between the maximum and minimum temperatures from the start to the end of film formation on the film roll. A transparent conductive film was obtained by subjecting the film having the transparent conductive layer laminated thereon to a heat treatment shown in Table 4. The properties of the obtained transparent conductive film are shown in Table 5.

[0107] Comparative Examples 1 to 8 A transparent conductive film was produced in the same manner as in Examples 1 to 7, except that a laminate film produced under the conditions shown in Tables 1 to 3 was used to form a transparent conductive film under the conditions shown in Table 4. In Comparative Example 7, a sintered target of indium oxide not containing tin oxide was used as target 4 instead of a sintered target of indium-tin composite oxide. The properties of the obtained transparent conductive film are shown in Table 5. In Comparative Example 6, unevenness and white spots due to oligomer precipitation were confirmed. In Comparative Example 8, the evaluation of uniformity was NG, which is presumably due to the fact that the coating liquid for the functional layer was difficult to wet the transparent plastic film substrate due to two points: there was no easy-adhesion layer on the functional layer side and the amount of leveling agent in the functional layer was small.

[0108] In Table 4, "*1" means that the test piece fell over and measurement was not possible.

[0109] [Table 4]

[0110] [Table 5] [Industrial Applicability]

[0111] Transparent conductive films can be used widely in electrical and electronic applications, such as for flat panel displays such as liquid crystal displays and electroluminescence (EL) displays, and as transparent electrodes in touch panels. [Explanation of symbols]

[0112] 1. Film to be processed 2 Center Roll 3. Chimney 4. Target 5. Transparent conductive film 6 Curing resin layer 7 Transparent plastic film substrate 8. Functional Layer 9A Easy adhesive layer 9B Easy adhesive layer 20 Transparent conductive film

Claims

1. A transparent conductive film comprising a transparent plastic film substrate and a transparent conductive film of an indium-tin composite oxide laminated on at least one surface of the substrate, the average arithmetic mean height (AVSa) of the transparent conductive film is 2 nm or more and 50 nm or less; the average maximum peak height (AVSp) of the transparent conductive film is 150 nm or more and 1000 nm or less; the average protrusion width on the transparent conductive film side surface and on the surface opposite to the surface on which the transparent conductive film is laminated, determined by the following Test Method 1, is 12 μm or less; A transparent conductive film, wherein the laminate strength of the transparent conductive film determined by the following Test Method 2 is 450 N / 15 mm or more. [Test method 1] Particle analysis is performed using a three-dimensional surface shape measuring device, Vertscan (measurement conditions: wave mode, measurement wavelength 560 nm, objective lens 50x, field of view 188.709 μm×141.496 μm) in the following steps (i) to (v). (i) The cross-sectional area of ​​all protrusions at a height of 0.1 μm from the lowest point on the measurement surface (T c This measurement is performed on both the transparent conductive film side surface and the surface opposite to the surface on which the transparent conductive film is laminated, and the sum of the cross-sectional areas of all protrusions on the transparent conductive film side surface and the surface opposite to the surface on which the transparent conductive film is laminated is defined as the cross-sectional area of ​​all protrusions (T c ) (ii) The average cross-sectional area of ​​all protrusions (the total number of protrusions is N p Then, T c / N p ) is required. (iii) Mean value (T c / N p ) or more than 10 times the cross-sectional area of ​​the average value (T c / N p ) is excluded. (iv) From the protrusions remaining in (iii), the top 20% and bottom 20% of the protrusions in order of largest cross-sectional area are further removed. (v) For the protrusions remaining in (iv), the average cross-sectional area (A) is calculated, and this value is substituted into the following formula (1) to calculate the average protrusion width (B). Formula (1): Average protrusion width (B) = 2 × (A ÷ π) 0.5 [Test method 2] A urethane-based two-liquid curing adhesive (containing 4% by mass of ethyl acetate as a solvent) is applied to the transparent conductive film side surface of the transparent conductive film using a wire bar #5, and then heated at 60° C. for 1 minute. The adhesive-coated surface of the transparent conductive film and the PET surface of a PET film (thickness 100 μm) are then laminated at 60° C. by a dry lamination method (0.3 MPa, width 70 cm), and aged at 40° C. for 4 days to obtain a laminate for evaluation. The obtained laminate is cut into a width of 15 mm and a length of 150 mm to obtain a test piece, and a T-peel test is performed under conditions of a temperature of 23° C., a relative humidity of 65%, and a peel speed of 100 mm / min to measure the maximum load.

2. The transparent conductive film has a thickness of 10 nm or more and 100 nm or less, The transparent conductive film has a tin oxide concentration of 0.5% by mass or more and 11% by mass or less, The static friction coefficient of the transparent conductive film is 1.00 or less, The transparent conductive film according to claim 1 , wherein the transparent conductive film has a dynamic friction coefficient of 0.80 or less.

3. 3. The transparent conductive film according to claim 1, wherein the transparent conductive film has a crystallinity of 70% or more.

4. A curable resin layer is provided between the transparent plastic film substrate and the transparent conductive film, The transparent conductive film according to claim 1 or 2, further comprising a functional layer on the opposite side of the transparent plastic film substrate to the side on which the transparent conductive film is present.

5. The transparent conductive film according to claim 4 , wherein the curable resin layer contains at least one type of particles selected from inorganic particles and organic particles.

6. The transparent conductive film according to claim 4 , wherein the functional layer has a static friction coefficient of 0.70 or less and a dynamic friction coefficient of 0.50 or less.

7. The transparent conductive film according to claim 4 , wherein the functional layer contains at least one type of particles selected from inorganic particles and organic particles.

8. The transparent conductive film according to claim 1 or 2, which has an easy-adhesion layer on at least one side of the transparent plastic film substrate.

9. The transparent conductive film according to claim 4 , wherein an easy-adhesion layer is disposed either between the transparent plastic film substrate and the curable resin layer or between the transparent plastic film substrate and the functional layer, or both.

Citation Information

Patent Citations

  • JP1974061697A

  • Case mounting device

    JP1989025598A